Proceedings 2016 Network and Distributed System Security Symposium 2016
DOI: 10.14722/ndss.2016.23082
|View full text |Cite
|
Sign up to set email alerts
|

Free for All! Assessing User Data Exposure to Advertising Libraries on Android

Abstract: Many studies focused on detecting and measuring the security and privacy risks associated with the integration of advertising libraries in mobile apps. These studies consistently demonstrate the abuses of existing ad libraries. However, to fully assess the risks of an app that uses an advertising library, we need to take into account not only the current behaviors but all of the allowed behaviors that could result in the compromise of user data confidentiality. Ad libraries on Android have potential for greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 38 publications
2
58
1
Order By: Relevance
“…Second, apps commonly incorporate advertising libraries, which means they effectively share their privileges with advertisers, weakening the “least privilege” principle and opening the threat of privacy leakage via advertising libraries. 12 Research challenge: clarify threats to, and develop security and privacy protections for, smartphone apps that handle medical and health data—in particular, develop methods to isolate apps from advertisers.…”
Section: Mhealth Smartphone Appsmentioning
confidence: 99%
“…Second, apps commonly incorporate advertising libraries, which means they effectively share their privileges with advertisers, weakening the “least privilege” principle and opening the threat of privacy leakage via advertising libraries. 12 Research challenge: clarify threats to, and develop security and privacy protections for, smartphone apps that handle medical and health data—in particular, develop methods to isolate apps from advertisers.…”
Section: Mhealth Smartphone Appsmentioning
confidence: 99%
“…We rely on the Apktool to reverse engineer Android apk files and generate smali code. 11 We defined a set of rules to capture the symptoms of each security smell. In particular, we utilize Java XML Parser for parsing the Manifest files and use regular expressions to define and match the code pattern corresponding to the identified symptoms of each smell in the code.…”
Section: Empirical Studymentioning
confidence: 99%
“…Additionally, researchers demonstrated that users were often surprised by the ability of applications to collect personal data in the background and share data with third parties [8]. Advertising libraries for example have been consistently examined for data exposure and leakages; a recent study revealed a trend in advertising networks to become more aggressive in collecting reachable user data [9].…”
Section: Related Workmentioning
confidence: 99%